Integrating layout planning and simulation for logistic nodes - Anne Kathrina Schwientek; Ann-Kathrin Lange; Markus Holzner; Margit Thomsen; Carlos Jahn (Logistics 4.0 and Sustainable Supply Chain Management: Innovative Solutions for Logistics and Sustainable Supply Chain Management in the Context of Industry 4.0. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 26, 2018)
When a new logistic node (e.g. a terminal) is planned or needs to be optimized, layout planning and simulation analysis are typically two separate tasks. While layout planning is an intuitive and visual but static approach, simulation is dynamic but more complex. Integrating both approaches would be highly beneficial. The idea of the integrated tool is to create first a static layout on a touchscreen planning table. After inserting relevant parameters and selecting preferred logistic strategies, the layout is converted directly into an executable simulation model. Based on the simulation, e.g. different layout or equipment variations can be tested. Main challenges for a successful integration are the logistic processes and strategies on the terminal. Both are not included in the layout planning, but are essential for a valid and realistic simulation model. Therefore, relevant process and strategy variations as well as typical research questions are defined. The integrated approach is an innovative solution to optimize planned as well as existing terminals. Typically, conducting layout planning and simulation studies separately is a very time consuming task. Integrating both is more efficient, closer to reality and more cooperative by allowing to involve more stakeholders at an earlier stage.
urn:nbn:de:gbv:830-88223699; 10419/209195; https://econpapers.repec.org/RePEc:zbw:hiclpr:26
Keywords: 650; Simulation; Layout Planning; Inland Waterway Container Terminal; Intermodal Transport